2023
DOI: 10.1177/10497323231214114
|View full text |Cite
|
Sign up to set email alerts
|

Living With Endometriosis: A Reflexive Thematic Analysis Examining Women’s Experiences With the Irish Healthcare Services

Ayisha Lightbourne,
Sarah Foley,
Maria Dempsey
et al.

Abstract: Endometriosis is an incurable chronic condition associated with debilitating pain and subfertility, affecting 1 in 10 women. The current study aims to explore the perceptions and experiences of women with endometriosis regarding the diagnosis, support and treatment options available in Ireland. It will further determine whether additional supports or improvements are needed to care well and effectively for women with this disease in the Irish healthcare system. A qualitative study design was deemed most suitab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…A systematic review of the psychological impact of medical gaslighting on women ( 15 ) found the healthcare experiences of women to be overwhelmingly negative and encompassing medical gaslighting, leading to delayed diagnosis, the need for self-advocacy, worsening health conditions and trauma ( 15 ). Experiencing medical gaslighting can lead to women suppressing emotion in clinical settings out of fear of being stigmatised and dismissed ( 35 ), using comprehensive self-management and communication strategies, and self-advocacy in an effort to get needs met and avoid further inequity ( 15 , 34–36 ), feeling that symptoms must need to be severe in order to warrant seeking medical care ( 36 ), and feelings of grief and loss from years spent undiagnosed and untreated ( 37 , 38 ). Due to medical gaslighting, women may also distrust, fear and avoid health services ( 17 , 32 , 34 , 39 ), and under-report their symptoms ( 40 ).…”
Section: Existing Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review of the psychological impact of medical gaslighting on women ( 15 ) found the healthcare experiences of women to be overwhelmingly negative and encompassing medical gaslighting, leading to delayed diagnosis, the need for self-advocacy, worsening health conditions and trauma ( 15 ). Experiencing medical gaslighting can lead to women suppressing emotion in clinical settings out of fear of being stigmatised and dismissed ( 35 ), using comprehensive self-management and communication strategies, and self-advocacy in an effort to get needs met and avoid further inequity ( 15 , 34–36 ), feeling that symptoms must need to be severe in order to warrant seeking medical care ( 36 ), and feelings of grief and loss from years spent undiagnosed and untreated ( 37 , 38 ). Due to medical gaslighting, women may also distrust, fear and avoid health services ( 17 , 32 , 34 , 39 ), and under-report their symptoms ( 40 ).…”
Section: Existing Evidencementioning
confidence: 99%
“…Due to medical gaslighting, women may also distrust, fear and avoid health services ( 17 , 32 , 34 , 39 ), and under-report their symptoms ( 40 ). This can increase vulnerability to illness, for example via delayed diagnosis ( 16 , 38 ), and worsening symptoms ( 15 , 17 ).…”
Section: Existing Evidencementioning
confidence: 99%